International commitments on domestic procurement laws: evaluating the compliance level of Nigeria to the agreement on government procurement of world trade organisation (2015)
This article examines the extent of compliance of Nigerian procurement law with the agreement on government procurement of WTO (WTO GPA). It notes that while Nigerian law can be said to be in full compliance with the demands of the 2011 UNICITRAL Model Law, the same could not be said of Revised WTO GPA as Nigerian law provides domestic preferences to her domestic bidders in violation of nondiscrimination requirements contained in WTO trade agreements. It discusses how liberalisation of public procurement between unequal states can lead to adverse economic problems and how such problems can be averted if developing countries take full advantage of special and differential treatment of WTO GPA. Since Nigeria is a member of WTO, it considers the possibility of Nigeria acceding to WTO GPA and how it can still protect its local suppliers by adopting a sustainable development approach in opening up its public procurement contracts to foreign markets.